Enhancing National Chi Nan University Campus’s Ecological Friendliness by Creating a Butterfly Habitat Using Reclaimed Water - Dong-Sing Wuu; I-Chung Liu; Ku-Fan Chen; Chih-Chi Yang; Yung-Pin Tsar; Yu-Chu Feng (Journal of Sustainability Perspectives, 2022)
The campus of National Chi Nan University (NCNU), Taiwan is about 150 hectares, and surrounded by dense valleys and forests that provides a habitat for many wild animals. In order to further enhance the ecological friendliness of the campus, the school implemented courses to create habitats for butterflies around the Sun Pond in the campus. The reclaimed water, originated from Water Treatment Factory, in the Sun Pond is used to irrigate the vegetation in the habitat to enhance the ecological conservation value. From 2019 to 2020, a number of 17 species with 670 individuals and food plants for butterflies was planted, and special instruction signs focusing on butterfly ecology were set up, so that staff and students can better understand the actions and goals in ecological conservation of green university. From 2020 to mid-2021, a total of 6 courses with 750 students (13% of the total number of students) visited the wonderful habit. The number of 22 species of butterflies was recorded in the habitat and this number was an average of 132 per 30 minutes, which shows that the construction of the habitats is successful. The creation of the butterfly habitat is in line with United Nations Sustainable Development Goal (SDG) 6 and SDG 15. The habitat has become a distinguished place for environmental education in the university. In the future, more community residents and tourists can experience this fantastic place and realize the efforts and achievements in ecological conservation succeeded by NCNU.Keyword: Butterfly Habitat, Reclaimed Water, Green University, Environmental Education, Community Resident.